Electrochromic Properties of WO3-MoO3 Nanocomposite Films Prepared by Electrodeposition Method - Song, Xu Chun; Wang, Xia; Zheng, Yi Fan; Yin, Hao Yong (Current Nanoscience, 2013)
WO3-MoO3 nanocomposite films with good electrochromic properties were prepared by the electrodeposition method. The surface morphologies and composition of the composite films were characterized by scanning electron microscope (SEM) and energydispersive X-ray analysis (EDS). Spectroelectrochemistry and electrochromic properties of the WO3-MoO3 nanocomposite films were characterized using cyclic voltammetry (CV) and spectral optical absorbance. The effect the content of MoO3 in the composite films on the electrochromic properties has been studied. It has been observed that the electrochromic properties of the composite films could be adjustable by changing the MoO3 quantity in the composite films.
Keywords: electrochromic